To convert the given polar equation to rectangular form, here are the steps.
1. Remember that sec θ = 1/cos θ. This means, the given polar equation can also be written as:
![r=(-3)/(\cos \theta)](https://img.qammunity.org/2023/formulas/mathematics/high-school/5kftom38p4dplj898osl7gsuwrkq6z6amx.png)
2. We can multiply cos θ to both sides of the function to remove the cos θ in the right side.
![\begin{gathered} r(\cos \theta)=(-3)/(\cos\theta)(\cos \theta) \\ r\cos \theta=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/nk8ul56n9d891asrjzwkozibuio8js68rb.png)
3. Since we know that x = r cos θ, we can say that x = -3. This is the rectangular form of the equation.
![x=-3](https://img.qammunity.org/2023/formulas/mathematics/college/hpwwzsayzig9ws40tupwhkcnkxbhs4gyhs.png)